Pregnancy outcomes of women who received conservative therapy for endometrial carcinoma or atypical endometrial hyperplasia. (1st June 2018) - Matsuzaki, Toshiya; Iwasa, Takeshi; Kawakita, Takako; Yamamoto, Yuri; Abe, Akiko; Hayashi, Aki; Yano, Kiyohito; Nishimura, Masato; Kuwahara, Akira; Irahara, Minoru
Abstract: Case: Approximately 3%‐25% of cases of endometrial carcinoma (EC) or atypical endometrial hyperplasia (AH) occur in women aged <40 years and conservative treatment with high‐dose medroxyprogesterone acetate (MPA) is administered to women who wish to preserve their fertility. Here is reported the pregnancy outcomes of patients with EC or AH who received MPA therapy at Tokushima University Hospital, Tokushima, Japan. The frequency of pregnancy and live births among the patients with EC or AH who received conservative treatment, followed by fertility treatment, were analyzed retrospectively. Outcome: Twelve patients underwent fertility examinations and received fertility treatment immediately after the completion of conservative treatment for EC or AH. One patient had the complication of severe diabetes and total embryo cryopreservation was performed before her diabetes was treated. Among the other 11 patients, 8 (72.7%) became pregnant at least once and 6 (54.5%) experienced at least 1 live birth. Three patients (25.0%) suffered disease recurrence during or after the infertility treatment and all of the recurrences occurred in the EC cohort. Conclusion: When patients with EC or AH wish to preserve their fertility, it is recommended that prompt and effective fertility treatment, including assisted reproductive technology, should be initiated just after conservative treatment because EC and AH exhibit relatively high recurrence rates among conservatively treated patients.